Aplicação de técnicas de CFD no estudo da eficiência de estágio em colunas de destilação para produção de etanol - Oliveira, Gladson Cintra de (2014)
Distillation is one of the most important and used separation techniques of components at industrial level, applied in a wide range of processes. Its great importance is due to the capacity of purify components of a mixture using the volatility difference among them as driving force. However, this technique represents 40% of the total energy consumption of an industrial facility. Nowadays, with the necessity of rethink the energetic use owing to the massive usage of natural resources, new regulations of pollutant emissions, environmental issues and market competition; the enhancement of the distillation process has become essential to the refineries, petrochemicals and a variety of other sectors of the industry. Empirical studies about the flow dynamics in distillation columns are rare due to the large dimensions of this equipment and the high investment, including measurement instrumentation. This lack of experimental data makes difficult the appropriate understanding of the mechanisms that occur in this equipment, as flow patterns and degree of separation, as well as the relation between both. Nevertheless, to improve the distillation process performance is necessary to deeply know the dynamics of the multiphase flow existing on each tray of the column, where the contact between the phases indeed happens. In this study, was proposed the computational simulation of sieve trays of distillation columns using CFD s tools (Computational Fluid Dynamics). The main aim was to conceive a model capable to predict the hydrodynamics and the more volatile component transfer between the liquid and the vapor. Furthermore, the regions that possibly interfere on obtaining higher efficiencies were pointed out. For that, tridimensional, transient and multiphase models with the Euler- Euler framework were used. The main results show liquid velocity profiles, volumetric fraction, clear liquid height, mass fraction and efficiency. The results presented agreement with the literature. In general, the fluid dynamics results obtained here highlight the significance of the application of models that represent the complex behavior existing on sieve trays, since this crucially influence in the separation degree of the process. The CFD evidenced to be and valuable tool to study this sort of flow on columns internals and can be applied in the design and optimization of those equipment.